VALIDITY OF LEARNING MODULE CONTAINING INFORMATION ABOUT ANTICHOLESTEROL ACTIVITY OF SAWI DAYAK (Elephantopus mollis) ON CIRCULATORY SYSTEM DISORDER - Novia Dian Kartika Wulandari; Ruqiah Ganda Putri Panjaitan; Andi Besse Tenriawaru (ATRIUM PENDIDIKAN BIOLOGI, 2022)
This research is development research, which aimed to create module of circulatory system disorder based on anti-cholesterol activity tests of Sawi Dayak - Elephantopus mollis. The data analysis use Content Validation Index (CVI) and Content Validation Rate (CVR) refers to Lawshe's method. The development of this module is in two stages: creation and validation of the module. Validator was selected based on a purposive sampling that involve two biology education experts of Universitas Tanjungpura, and three biology teachers. Presentation, graphic, content, and language aspects were evaluated, total 24 criterias. Based on the results data analysis, CVI was 0.99 in the valid category and all criteria CVR was 0.99. It was concluded that the product is suitable as teaching material for the circulatory system disorder sub-material for senior high school.